A biodynamic model predicting waterborne lead bioaccumulation in Gammarus pulex: Influence of water chemistry and in situ validation. (August 2015) - Urien, N.; Uher, E.; Billoir, E.; Geffard, O.; Fechner, L.C.; Lebrun, J.D.
Abstract: Metals bioaccumulated in aquatic organisms are considered to be a good indicator of bioavailable metal contamination levels in freshwaters. However, bioaccumulation depends on the metal, the species, and the water chemistry that influences metal bioavailability. In the laboratory, a kinetic model was used to describe waterborne Pb bioaccumulated in Gammarus pulex . Uptake and elimination rate constants were successfully determined and the effect of Ca 2+ on Pb uptake was integrated into the model. Thereafter, accumulated Pb concentrations in organisms were predicted with the model and compared with those measured in native populations from the Seine watershed (France). The predictions had a good agreement with the bioaccumulation levels observed in native gammarids and particularly when the effect of calcium was considered. To conclude, kinetic parameters experimentally derived for Pb in G. pulex are applicable in environmental conditions. Moreover, the consideration of the water's chemistry is crucial for a reliable interpretation of bioaccumulation. Highlights: Kinetic model was used to describe waterborne Pb bioaccumulation in G. pulex . Ca 2+ inhibits Pb uptake by G. pulex in the laboratory. Model predictions were compared to bioaccumulated Pb in native G. pulex . Model accurately predicts waterborne bioaccumulated Pb in gammarids. Considering the influence of Ca 2+ improves the model predictions in the field. Abstract : An experimentally-derived kinetic model considering the effect of calcium was relevant to predict the waterborne Pb bioaccumulation in native Gammarus pulex .